Chapter Sarazenen als "Fremde"? Anmerkungen zum Islambild in der abendländischen Geschichtsschreibung des frühen Mittelalters - Goetz, Hans-Werner (De Gruyter, 2009)
The subjects of this volume are views and perceptions of the "other" (i.e. strangers, enemies or curiosities) within the Islamic world, as well as in the interplay between the Islamic and non-Islamic worlds. More than 20 contributions describe conceptions and contingencies of the other from very different perspectives, so arriving - with reference to Islam - at insights into the complex problems of the "other." The studies are dedicated to Professor Gernot Rotter.